Microbacterium spp. peritonitis in patients undergoing peritoneal dialysis: a single-center experience and literature review - Yu, Xiao; Li, Zhao; Yang, Xinbo; Wang, Xiaopei; Nan, Di; Lu, Wanhong; Lv, Jing; Ma, Ying (Frontiers in Medicine, 2023)
Introduction Peritoneal dialysis-related peritonitis (PDRP) caused by Microbacterium spp. is very rare, with only 9 cases reported to date. In this study, we report the treatment experiences of 7 patients at our peritoneal dialysis center. Methods We retrospectively collected clinical characteristics and antibiotic management of all 7 episodes of PDRP caused by Microbacterium spp. in 7 patients from at our center over 4 years, and reviewed the documented Microbacterium spp. PDRP in the literature. Results Empiric antibiotic therapy was initiated as soon as possible, and consisted of intraperitoneal (IP) gentamicin in combination with vancomycin. After up to 5 days, gentamicin was changed to meropenem if the treatment was not effective. The intended course of antibiotic treatment was 21-day. Totally, 6 episodes were cured (85.7%), which was higher than reported. Conclusion The 21-day antibiotic therapy program by combining vancomycin and meropenem may benefit the management of Microbacterium spp. PDRP.